The effectiveness of fibrolytic enzymes and active yeast on improving reticulorumen pH in dairy cows. - Šilinskas, I; Monkevičienė, I; Tapio, I; Musayeva, K; Japertienė, R; Kerzienė, S; Dovydaitienė, G; Sederevičius, A; Želvytė, R. (Polish Academy of Sciences Committee of Veterinary Sciences ; University of Warmia and Mazury in Olsztyn, 2020)
Exogenous fibrolytic enzymes (EFE) and yeast are feed supplements that improve forage digestion in rumen, but their influences on physical reticulorumen parameters are not well studied. This study was designed to evaluate the effect of the EFE:endo-β-xylanase (37x104 U/cow/day), endocellulase (45x104 U/cow/day), endo-β-glucanase (12x104 U/cow/day), and active yeast – Saccharomyces cerevisiae CNCM-1077 (10x109 CFU/cow/day) supplements on reticulorumen pH (RpH) and temperature (RT) in dairy cows. Nine Lithuanian Red cows were allocated into three groups (3 cows/group): control group (C) – farm diet without supplementation, enzyme group (E) – farm diet supplemented with EFE, enzyme and active yeast group (EY) – farm diet supplemented with EFE and active yeast. The feeding trial lasted for 60 d. All cows were equipped with reticuloruminal telemetric pH and temperature sensor device. Data provided by the device were used to calculate the mean RpH (RpH/24h), the mean minimal RpH (minRpH/24h) and mean of the time that RpH was below the threshold value of 6.0 (RpH<6.0/24h, min.). The highest RpH/24h (6.37±0.22) was observed in group EY and it was by 1.62% (p<0.05) and 1.27% (p<0.001) higher as compared with groups E and C, respectively. Also minRpH/24h (6.24±0.24) was highest in group EY and values were by 0.63% (p<0.001) and 0.65% (p<0.001) higher as compared with groups C and E, respectively. The shortest duration of RpH<0.05) and 47.87% shorter as compared with groups C and E, respectively. In conclusion, feed supplementation with EFE and Saccharomyces cerevisiae CNCM-1077 had beneficial effect on RpH.
Keywords: exogenous fibrolytic enzymes; active yeast; reticulorumen pH; dairy cow